History of the Czechoslovak Tourist Society Between 1938–1948 - Tlustý, Tomáš; Kursová, Vlasta (Sport and Tourism Central European Journal, 2024)
The present paper focuses on one of the less known Czechoslovak tourist organisations. The Czechoslovak Tourist Society was formed relatively late in comparison with the other tourist organisations active in Czechoslovakia, namely in the year 1925. Its membership consisted mainly of members of the middle and lower walks of life of the nation. Accordingly, its primary objective was to offer the less well-off classes cheap participation in group tours, visits to natural beauties of Czechoslovakia or recreational stays in spas, all at minimal membership fees. The membership base of the Czechoslovak Tourist Society had gradually grown, reaching as many as 30 thousandmembers in the period under review. Its members were involved in resistance activities during the Nazi occupation. The Society intended to follow up on its approach to occupiers after the end of the war, when they attempted to gain the leading role among Czechoslovak tourist associations, which increasingly discussed the creation of a unified Czechoslovak tourist organisation. The Czechoslovak Tourist Society lost its independence in 1948, when it was – like other Czechoslovak physical education, sports and tourist organisations – incorporated intoSokol by communists.